2012
DOI: 10.3844/ajassp.2012.1518.1526
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Job Satisfaction and Turnover Intention

Abstract: Problem statement: The objective of this study were to determine the effect of job satisfaction on turnover intentions among the employees in XYZ Sdn. Bhd, Malaysia. Approach: A total of 32 set of complete questionnaires gathered from executives and non-executives of a local printing company were involved in the study and 32 completed the questionnaires. Using structured questionnaires in a controlled environment, the results manage to extract both intrinsic and extrinsic job satisfaction that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…Turnover intention can be a good proxy for measuring actual turnover because the latter can be difficult to measure (Hayes et al, 2006). Numerous studies (e.g., Kalliath & Beck, 2001;Kramer, Callister, & Turban, 1995;Mahdi et al, 2012;Price & Mueller, 1981) have been conducted to understand what determines employees' turnover intentions. Nonetheless, a single, broadly accepted, comprehensive model of turnover is still lacking (Gieter, Hofmans, & Pepermans, 2011).…”
Section: Turnover Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Turnover intention can be a good proxy for measuring actual turnover because the latter can be difficult to measure (Hayes et al, 2006). Numerous studies (e.g., Kalliath & Beck, 2001;Kramer, Callister, & Turban, 1995;Mahdi et al, 2012;Price & Mueller, 1981) have been conducted to understand what determines employees' turnover intentions. Nonetheless, a single, broadly accepted, comprehensive model of turnover is still lacking (Gieter, Hofmans, & Pepermans, 2011).…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Researchers believe that job satisfaction can influence work productivity, employee turnover, absenteeism and life satisfaction (Spector, 2008). Several studies have found that job satisfaction has a positive relationship with all three dimensions of organizational commitment and an inverse relationship with turnover intention (Aydogdu & Asikgil, 2011;Mahdi et al, 2012;Yucel, 2012). Moreover, research has found that job satisfaction may be the most important construct in attempting to understand turnover (Ghiselli, Lopa, & Bai, 2001).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unfavorable working condition for a nurse may reduce the satisfaction of a nurse, and therefore will interfere with efforts to improve patients’ satisfaction because high quality nursing care is usually a result of high levels of job satisfaction [4]. In today’s world, the importance of evaluating the patient satisfaction as one of the main criteria to determine the healthcare quality is evident [5] and nursing care is one of the main factors of patient satisfaction regarding the quality of the healthcare [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…3;2014 direct negative significant impact on turnover intention. Past studies have obtained similar result (Mahdi, et al, 2012;Egan et al, 2004;Farrell and Rusbult, 1981) Thus, a negative relationship between Job satisfaction and turnover intention means that the employees have intent to leave the current work if they not satisfied in future.…”
Section: Discussionmentioning
confidence: 63%